2021
DOI: 10.1101/2021.08.31.458457
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust, data-driven bioregionalizations emerge from diversity concordance

Abstract: Aim: Despite the increasing interest in developing new bioregionalizations and assessing the most widely accepted biogeographic frameworks, no study to date has sought to systematically define a system of small bioregions nested within larger ones that better reflect the distribution and patterns of biodiversity. Here, we examine how an algorithmic, data-driven model of diversity patterns can lead to an ecologically interpretable hierarchy of bioregions. Location: Australia. Time period: Present. Major taxa st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(109 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have shown that differences in spatial scales have different effects for evaluating diversity (Chisholm et al, 2018). However, our knowledge of bioregional-scale diversity is fragmented, creating barriers to systematic conservation planning, and knowledge gaps about diversity at spatial scales deserve more attention (Montalvo-Mancheno et al, 2020). Crawley and Harral proposed that at large spatial scales, species richness depends on the number of species and extinction rates.…”
Section: The Importance Of Analysis At Different Spatial Scalesmentioning
confidence: 99%
“…Previous studies have shown that differences in spatial scales have different effects for evaluating diversity (Chisholm et al, 2018). However, our knowledge of bioregional-scale diversity is fragmented, creating barriers to systematic conservation planning, and knowledge gaps about diversity at spatial scales deserve more attention (Montalvo-Mancheno et al, 2020). Crawley and Harral proposed that at large spatial scales, species richness depends on the number of species and extinction rates.…”
Section: The Importance Of Analysis At Different Spatial Scalesmentioning
confidence: 99%
“…We used the mammal community in Tasmania (Australia) as a case study to assess the impact of anthropogenic land-use on the architecture of food webs in an invaded community. Tasmania has a relatively uniformly distributed community of mammal species (Chiu-Werner A., Montalvo-Mancheno C.S., Driessen M., Jones M.E., unpublished data; Montalvo-Mancheno et al, 2021), but the abundance of each species varies geographically. For instance, the disease-induced decline of populations of the top predator and scavenger, the Tasmanian devil (Sarcophilus harrisii), has triggered a rise in feral cat (Felis catus) numbers through reduced competition and increased presence of carrion in the landscape (Cunningham et al, 2018(Cunningham et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%